PENYULUHAN FORMULASI SEDIAAN SERBUK TABUR PERONA PIPI EKSTRAK ETANOL BUAH SEMANGKA (Citrullus lanatus) - Sari Theresia Bukit; Dewi Kartika; Jhon Patar Sinurat (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LP2M) Institut Kesehatan Medistra Lubuk Pakam, 2021)
One of the fruits in Indonesia that can be used in the cosmetic sector is watermelon. Its red color indicates the high content of lycopene, a natural pigment as a coloring agent in decorative cosmetic formulations, especially blusher. The purpose of this study was to determine whether watermelon extract can be used as a dye in blusher preparations and to determine the formulation of watermelon (Citrullus lanatus) blusher does not cause skin irritation when used. The extract was obtained by maceration using 96% ethanol. The blush formula uses dye from watermelon with a concentration of 15%, 20%, and 25%. The evaluation of preparations includes homogeneity, organoleptic, irritation test, pH test. The results showed that homogeneity, organolepti, and pH of the preparation remained stable for 14 days of storage. The results of the irritation test did not show any irritation.